Ukraine and Lithuania: A comparative study of early military-political integration trajectories in the Post-Soviet Era - Mykhaylyk, Vitaliy; Kadeniuk, Oleksandr; Sapytska, Olena; Mykhaylyk, Olena (Research Journal in Advanced Humanities, 2023)
This article presents a comparative analysis of the initial vectors of military-political integration of Ukraine and Lithuania following the dissolution of the Soviet Union, offering a novel scholarly examination of the topic. The authors draw upon historical context, analyze international and domestic political processes, and consider institutional and geopolitical factors. The article explores the causes, strategies, and challenges faced by both countries in their attempts to integrate into NATO, the European Union, and other international military-political structures. Specific features of each country are analyzed, revealing their unique characteristics for comparative study and contribution to the field. The significance of the research lies in identifying and comparing the key drivers of military-political integration in Ukraine and Lithuania in order to discern similarities and differences, as well as to understand the developmental peculiarities of each nation within the post-Soviet space. The findings and conclusions of the article contribute to a better understanding of the vectors of military-political integration of Ukraine and Lithuania and may also be useful for studying and comparing integration processes in other post-Soviet states, therefore contributing to the development of scientific understanding of integration processes within the context of shifting geopolitical realities.